A1 SEMAPHORIN3E (SEMA3E) REGULATES INTESTINAL INFLAMMATION THROUGH THE MODULATION OF DENDRITIC CELLS FUNCTIONS. (1st March 2018) - Kermarrec, L; Eissa, N; Bernstein, C N; Ghia, J
Abstract: Background: Inflammatory bowel diseases (IBD) involve an increase of dendritic cells (DC) infiltration and cytokines production. Recently, semaphorins have been implicated in inflammation and cell migration and has emerged as an essential axis in DC immune responses. Aims: This study aims to determine the role of Sema3E on DC regulation during colitis using, clinical rectal biopsies from active ulcerative colitis (UC), a murine model of colitis and, DC cell culture. Methods: mRNA expression level of Sema3E was determined in human rectal biopsies collected from healthy (n=7) and active UC patients (n=7) using RT-qPCR, and an absolute correlation analysis was conducted against pro- and anti-inflammatory markers. Bone marrow-derived DCs (BMDC) were isolated from naïve C57BL/6-deficient (Sema3E -/- ) and wild-type (WT) mice, and differentiation, IL-12p40 and interferon (IFN)-γ production were quantified by flow cytometry and/or ELISA. Colitis was induced by dextran sulfate sodium (DSS 5%) for 5 days in Sema3E -/- and WT mice treated or not with recombinant Sema3E-Fc. Disease activity index (DAI), macro- and microscopic scores were determined. Colonic myeloperoxidase (MPO) activity, Sema3E, TNF-α, IL-1β, IL-6, and IL-12p40 were quantified using ELISA. Splenocytes and splenic CD11C + cells were isolated from colitic groups then treated with Sema3E (10 -6 M) or vehicle, and IL-12p40 and IFN-γ levels were assessed. Results: In active UC biopsies, Sema3E mRNA was significantly decreased and levels of Sema3E were negatively and positively correlated with pro- and anti-inflammatory cytokines. In naïve mice, Sema3E deficiency resulted in an increase of DC differentiation, migration and antigen uptake, and CD11C + BMDC showed an increase of the intracellular IL-12p40. In colitic WT mice, Sema3E level was significantly decreased. In colitic Sema3E -/- mice, DAI, macro- & microscopic scores, colonic MPO activity, TNF-α, IL-1β, IL-6, IL-12p40, IFN-γ were significantly increased compared to wild-type and treatment with rSema3E-Fc abolished that deleterious effect. When compared to WT, in colitic conditions, SemaE -/- splenocytes and splenic CD11C + cells showed an increased production of IL-12p40 and IFN-γ, and rSema3E-Fc treatment of splenic CD11C + decreased them. Conclusions: Sema3E signaling is critical in the pathogenesis of inflammation in both the clinical and experimental setting through the modulation of DC migration and activation. These novel findings may pave the road toward novel therapeutic strategies in IBD targeting Sema3E. Funding Agencies: CCC, CIHRCFI